Mylomygale (Macroscelidea, Macroscelididae) from the Pliocene of South Africa. (December 2022) - Senut, Brigitte; Sénégas, Frank; Gommery, Dominique; Vilakazi, Nonhlanhla; Kgasi, Lazarus; Pickford, Martin
Abstract: The palaeokarst system of Bolt's Farm, Gauteng Province, South Africa, is endowed with numerous fossiliferous Plio-Pleistocene deposits. Among them, the mid-Pliocene locus of BPA (Brad Pit A) has yielded a hypsodont upper molar which exhibits a rodent-like wear pattern, but is not a rodent. In several aspects, it recalls macroscelidids and could fit in occlusal morphology with the lower teeth of Mylomygale spiersi, described on the basis of a mandible from Norlim Cave close to the Taung Limeworks, which yielded the holotype of Australopithecus africanus . This upper molar could be attributed to Mylomygale, a taxon represented by only three specimens. The hypsodonty of the molar and the wear pattern suggest that, at Bolt's Farm, Mylomygale was feeding on tough food and that some herbaceous patches might have occurred in the environment. Moreover our scans reveal that the holotype of Mylomygale possessed an m/3, previously unrecognized. Highlights: The paper interprets a new specimen from Pliocene deposits at Bolt's Farm (South Africa) attributed to  Mylomygale, an extinct genus of sengi. It is of special interest for two reasons -  Mylomygale is known by only two other specimens of uncertain age; the Bolt's Farm specimen is the first recorded upper tooth of this micro-cursorial mammal. The new specimen suggests that  Mylomygale  is possibly linked phylogenetically to Early Miocene Myohyracidae.